2002
DOI: 10.1080/03601270290081416
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Evaluating an Interdisciplinary Clinical Team Training Program: Lessons Taught and Lessons Learned

Abstract: P h i lli p G. Cla r kRh od e Isla nd Ger iat ric E du ca t ion Cen t er, U n iver sity of Rh ode Islan d, Kin gst on , Rh ode Isla n d, U SA Ma r ie M. Lei n h a a sRh od e Isla nd Ger iat ric E du ca t ion Cen t er, U n iver sity of Rh ode Islan d, Kin gst on , Rh ode Isla n d, U SA Ra c h el Fi lin s onRh ode Isla n d College, P roviden ce, Rh ode Isla n d, U SA The training of clinicians in working together as an interdisciplinary team has received growing support in geriatrics. Most teamwork training prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…In this way, the goals and objectives for teamwork training should be redefined from the old way of thinking about training as education in group processes and development to a much more flexible and dynamic conceptualization of teamwork (Clark et al . ), focusing on both relational and functional competence.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the goals and objectives for teamwork training should be redefined from the old way of thinking about training as education in group processes and development to a much more flexible and dynamic conceptualization of teamwork (Clark et al . ), focusing on both relational and functional competence.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies found no positive associations and one did not present clear outcomes concerning team effectiveness [30][31][32]. The other three studies found that interprofes- sional training resulted in improvements in team skills, team climate, awareness of professional roles, attitude, learning and retaining information, and morale.…”
Section: Interprofessional Trainingmentioning
confidence: 96%
“…On the other hand, not all learners felt that multiple contacts with the information was beneficial; some learners felt that the education would have been better suited to an earlier level learner, as they were already experienced in teamwork. These data begin to inform the issues raised by Clark et al [11] and Coogle [27] around IPE including the need to address the varying levels of learners, questions around the learning "dose" necessary to accomplish collaborative skills, and the need for a "continuum of teamwork training" to address the varying needs within and across pre-and postlicensure learners from different health care professions.…”
Section: Discussionmentioning
confidence: 91%
“…In North America, IPE programs have developed over the last two decades. The Hartford Foundation-funded Geriatric Interdisciplinary Team Training (GITT) [4][5][6][7][8][9][10] and Geriatric Education Centres (GEC) funded through the U.S. Bureau of Health Professions [11] created effective geriatric IPE initiatives throughout the United States. In 2005, Health Canada funded 20 projects across the country, which provided the stimulus for the development of IECPCP initiatives in Canada.…”
Section: Introductionmentioning
confidence: 99%